О засухоустойчивости декоративных яблонь из коллекции Донецкого ботанического сада НАН Украины - Закотенко, С.Н. (Промышленная ботаника, 2002)
The data on the comparative assessment of ornamental apple-trees drought-resistance in the wild and under laboratory conditions are cited. A number of indices of water regime (viz. water-retention capacity, moisture deficiency, renewal of turgor in leaves after withering) has been obtained. On the basis of visual observation a different individual response of the samples to soil and atmospheric water deficiency has been fixed being linked with the reducing of their ornamental qualities. A series of samples has been defined, capable of successful growth under the arid conditions of the Ukraine’s south-east practically without reducing of their ornamental qualities without any additional watering.